Calcareous nannofossils as a dating tool in shallow marine environment. An example from an upper Paleogene carbonate platform succession in the Mediterranean - Raffi, Isabella; RICCI, CRISTIANO; Garzarella, Adele; BRANDANO, Marco; CORNACCHIA, IRENE; TOMASSETTI, LAURA (Newsletters on Stratigraphy, 2016)
In this study, calcareous nannofossils have been used for refining the biostratigraphic classification and chronology of a neritic Paleogene sedimentary succession, outcropping in the Central Apennines (Italy) and belonging to the Santo Spirito Formation". Calcareous nannofossils are typically found in deep-sea sediments, but proved to be consistently present and useful also in these shallow -water deposits. The obtained biostratigraphic results benefitted from the random occurrence of rich and diversified nannofossil assemblages in chalky sediments, found inside chert nodules and as thin layers, within the dominant calcarenitic lithology of this lithostratigraphic unit. The observed well-preserved assemblages provided a reliable biostratigraphic framework that was completed with the analysis of intervening samples obtained from scattered layers of calcareous marls. In the two studied sections, Pennapiedimonte and Lettomanoppello sections, we recognize a series of biozones that integrate with the known biostratigraphy based on large and planktonic foraminifera. Overall, we provide a reliable chronology indicating that the stratigraphic succession of Santo Spirito Fm, in the investigated area, is constrained between similar to 42 Ma (late Lutetian) and similar to 31 Ma (early Rupelian). This precise strati graphic assignment extends of similar to 2 m.y. the time lapse of sedimentation of the middle and upper Santo Spirito Fm, previously considered in these sections as limited to upper Bartonian-lower Rupelian. The obtained more accurate chronology is helpful for an ongoing study addressed to perform a detailed sequence stratigraphic interpretation of the unit, specifically to recognize higher rank depositional sequences within it. Moreover, our data evidence that the Eocene/Oligocene transition, with the intervening large transient glaciation event "Oi-1, is represented in the sediments of S. Spirito Fm, suggesting that further studies in this area could provide new information on the response of this global ...